Begonia nahauensis (sect. Platycentrum, Begoniaceae), a new species from northern Vietnam - Bui, Doi The; Nguyen, Cuong Huu; Tran, The Ngoc; Nguyen, Ly Van; Lin, Che Wei (Phytotaxa, 2024)
A new species of Begonia sect. Platycentrum, Begonia nahauensis, is described based on morphological characters. The new species is morphologically similar to B. auritalata, however, it is clearly distinct from the latter due to its petioles and ovary, which are densely covered with gland-tipped hairs (vs. non-glandular hairs), capsule with three complete locules (vs. three locules, but one of them is either underdeveloped or degenerated) and three straight wings (vs. adaxial wing being concave). A morphological description and diagnosis, information on distribution and ecology, and a preliminary conservation assessment are provided.